COMPARISON OF ANTIFUNGAL EFFECTS OF 50% SIWAK (SALVADORA PERSICA) ETHANOL EXTRACT WITH NYSTATIN ORAL SUSPENSION ON CANDIDA ALBICANS BIOFILM (IN VITRO STUDY) - Ayatusyifa' Maghfyrany Sumarno; Rina Kartika Sari; Rahmawati Sri Praptiningsih (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Candida albicans is an opportunistic pathogen that grow and survive as a commensal. However, a number of predisposing factors can turn them into pathogens. Nystatin is an antifungal drug from the polyene group use to treat oral candidiasis. Siwak have various bioactive components that can affect oral health. Tannin, one of the chemical component of siwak, is known to have antifungal activity against Candida albicans. This study aim to compare the antifungal effect of 50% siwak and nystatin on the Candida albicans biofilm.Method: This research method was an experimental type with a post test only control group design with a sample of 36 divided into 2 groups: 50% siwak and nystatin. Each group was incubated for 24 hours. The formation of biofilms was measured by calculating Optical Density using an ELISA-reader. Data analysis was performed using the Independent T-test.Result: The results of the average optical density values obtained 50% siwak group was 2.64261 and nystatin group was 2.428. Independent T-test results obtained p = .138 (p> 0.05) which showed no significant difference in antifungal effects between 50% siwak and nystatin.Conclusion: This research showed that 50% siwak extract and nystatin had an equivalent antifungal effect in reducing in vitro growth of Candida albicans biofilms.